Research of the Load Distribution at the Meshing Point of Double Circular Arc Gear - Jiang Biqiong; Ren Zhongyi; Duan Jianzhong (Jixie chuandong)
The contact stress in different meshing point is not the same of double circular arc gear due to its different teeth numbers,tooth width and tooth bending deformation. A meshing point contact force mathematical model of double circular arc gear is established,the gear tooth bend stiffness is calculated according to mechanics of materials and the theory of elasticity. The numerical example is calculated to obtain the contact force in different meshing point of double circular arc gear of different tooth number,modulus and contact ratio.The basis for the tooth profile modification and improving the gear load capacity of double circular arc gear is provided by the research result.